Semantic Mapping or Rote Memorisation: Which Strategy Is More Effective for Students’ Acquisition and Memorization of L2 Vocabulary? - Badr, Haytham M. (2019)
The present paper aimed to compare the influence of two vocabulary teaching strategies on students’ vocabulary retention—roughly used in this paper to refer to the process of acquisition and memorisation. In particular, the strategies of semantic mapping and rote memorisation were compared and contrasted within a trail of evidence-based data gathered systematically from two ESL classes in an international school in the Emirate of Sharjah in the United Arab Emirates (UAE). The participants of the study were 30 male students who were in grade 12, the last stage of high school in the UAE educational system. The participants were randomly divided into two groups: a control group and an experimental group. In order to measure the impact of the two strategies under investigation on the students’ vocabulary retention, the two groups sat for a pre-test and a posttest. The intervention that took place between the two tests lasted for three weeks. The results showed that the students’ retrieval of the target vocabulary words improved as a result of implementing both strategies, but that the improvement which resulted from the use of semantic mapping overrode that which ensued from rote memorisation.